Digital radiographic image enhancement for weld defect detection using smoothing and morphological transformations / Suhaila Abdul Halim, Arsmah Ibrahim and Yupiter Harangan Prasada Manurung - Abdul Halim, Suhaila; Ibrahim, Arsmah; Prasada Manurung, Yupiter Harangan (Research Management Institute, 2012)
Accurate inspection ofweldedmaterials is important in relation to achieve acceptable standards. Radiography, a non-destructive test method, is commonly used to evaluate the internal condition ofa material with respect to defect detection. Thepresence ofnoise in low resolution ofradiographic images significantly complicates analysis; therefore attaining higher quality radiographic images makes defect detection more readily achievable. This paper presents a study pertaining to the quality enhancement of radiographic images with respect to different types of defects. A series of digital radiographic weld flaw images were smoothed using multiple smoothing techniques to remove inherent noise followed by top and bottom hat morphological transformations. Image quality was evaluated quantitatively with respect to SNR, PSNR andMAE. The results indicate that smoothing enhances the quality ofradiographic images, thereby promoting defect detection with the respect to original radiographic images.